Natural product manoalide promotes EGFR-TKI sensitivity of lung cancer cells by KRAS-ERK pathway and mitochondrial Ca2+ overload-induced ferroptosis - Ni, Yinyun; Liu, Jiaye; Zeng, Lingyan; Yang, Ying; Liu, Lei; Yao, Menglin; Chai, Li; Zhang, Lu; Li, Yi; Zhang, Li; Li, Weimin (Frontiers in Pharmacology, 2023)
Background: Manoalide (MA), a proven natural inhibitor of PLA2 has anticancer effects, but its potential application and mechanism as an anticancer drug to promote EGFR-TKI sensitivity in lung cancer cells have not been studied. Methods: KRAS-mutated lung cancer cells and organoids, acquired osimertinib-resistant lung cancer cell lines HCC827OR, were used as EGFR-TKI-resistant models. CCK-8, clone formation, apoptosis assays, and calcein-AM staining were performed to investigate the inhibitory effects of MA in lung cancer cells and organoids. The flow cytometry or confocal microscope was used to detect lipid droplets, ROS, lipid peroxidation, mitochondria Ca2+, and iron content. The oxygen consumption rate (OCR) and fatty acid oxidation (FAO) were used to estimate the effect of MA on mitochondrial function. Results: MA inhibits the proliferation of KRAS-mutated lung cancer cells and organoids. In addition, MA induces ER stress in a ROS-dependent mechanism. The ROS induced by MA is mainly in mitochondrial and causes lipid peroxidation, thereby inhibiting mitochondrial FAO metabolism and promoting the accumulation of lipid droplets. MA also suppresses the KRAS-ERK pathway through ROS and promotes the sensitivity of KRAS-mutated lung cancer cells and organoids to osimertinib. Furthermore, MA induces ferroptosis by suppressing the NRF2-SLC7A11 axis and mitochondrial Ca2+ overload induced-FTH1 pathways to promote the sensitivity of osimertinib-resistant lung cancer cells to osimertinib. Conclusions: MA is a candidate EGFR-TKI sensitizer in KRAS-mutated and osimertinib-resistant lung cancer cells.